2021
DOI: 10.3345/cep.2020.01704
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome and possible vertical transmission of coronavirus disease 2019: experience from North India

Abstract: Background: The consequences of SARS-CoV-2 on mother and fetus remain unknown due to a lack of robust evidence from prospective studies. Purpose: This study evaluated the effect of COVID-19 on neonatal outcomes and the scope of vertical transmission. Methods: This ambispective observational study enrolled pregnant women with COVID-19 in North India from April 1 to August 31, 2020 to evaluate neonatal outcomes and the risk of vertical transmission. Results: A total of 44 neonates born to 41 COVID-19-positive mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…One recent paper that reviewed findings from 101 women infected with SARS-CoV-2 reported that there is vertical transmission of SARS-CoV-2 from the mother to the infant, with adverse effects on the newborn [ 74 ]. However, two other papers reported negligible transmission [ 75 , 76 ]. However, transmission may not be required for the virus to induce neuroinflammation, as it may affect peripheral nerves [ 77 ] or the developing brain via the Spike protein directly affecting brain cells [ 78 ].…”
Section: Infections and Covid-19mentioning
confidence: 99%
“…One recent paper that reviewed findings from 101 women infected with SARS-CoV-2 reported that there is vertical transmission of SARS-CoV-2 from the mother to the infant, with adverse effects on the newborn [ 74 ]. However, two other papers reported negligible transmission [ 75 , 76 ]. However, transmission may not be required for the virus to induce neuroinflammation, as it may affect peripheral nerves [ 77 ] or the developing brain via the Spike protein directly affecting brain cells [ 78 ].…”
Section: Infections and Covid-19mentioning
confidence: 99%
“…[ 14 ] A study conducted on 44 neonates by Sharma R et al . [ 15 ] showed a negligible possibility of vertical transmission of the SARS-CoV-2 virus. The natural history of COVID-19 infection is not fully understood; many genetic mutations occur in the virus that might be more virulent, so more epidemiological investigations should be done.…”
Section: Introductionmentioning
confidence: 99%
“…Interesting results of the study of Sharma et al [ 2 ] included comparably high percentages of preterm deliveries (14.6%) and caesarean sections (56.1%) ( Fig. 1 ).…”
mentioning
confidence: 99%
“…Considerable studies have been conducted on these specific issues, and even though more studies need to be completed, studies to date assist with the shared decision-making of families and attending physicians. In this issue of Clinical and Experimental Pediatrics , Sharma et al [ 2 ] have explored these problems by an ambispective observational study that examined 44 neonates born to 41 SARS-CoV-2 positive mothers from North India. The results of the study showed no definite direct adverse effect on the fetus or newborn (perinatal outcome), and a negligible possibility of vertical transmission.…”
mentioning
confidence: 99%
See 1 more Smart Citation